Mechanics of carbon nanotubes : fundamentals, modeling and safety - Harik, Vasyl Michael (Academic Press, an imprint of Elsevier, 2018)
Mechanics of Carbon Nanotubes: Fundamentals, Modeling and Safety draws on the latest academic research and nanotechnology applications to provide a comprehensive guide on the most recent developments in the science of carbon nanotubes. The fundamentals of nanomechanics and mechanical behavior of carbon nanotubes are presented in initial chapters, followed by more advanced topics such as the classification of carbon nanotubes, carbon nanotubes in nanocomposites, multiwall carbon nanotubes, and recent trends. This book provides a system for the classification of carbon nanotubes into 20 classes, aiding correct selection for various applications, and includes the Atomic Registry Matrix Analysis for nanoscale interfaces, essential for design involving friction or sliding. Parametric maps are included to help readers pick the correct model for a particular CNT geometry, in addition to a thorough examination of the effective thickness paradox and safety issues related to CNTs, such as toxicity at high aspect ratio. Mechanics of Carbon Nanotubes is essential reading for anyone involved in research or engineering that includes carbon nanotubes, be they students or seasoned professionals in the field. It is particularly useful to those working with applications in the areas of microelectronics, robotics, aerospace, composites, or prosthetics.